Knowledge of Cooperative and Private Agri Input Dealers regarding Improved Barley Production Technology - Meena, Sunil Kumar; Dr. (Indian Journal of Extension Education, 2024)
The study assessed cooperative and private agri-input dealers’ knowledge regarding improved barley production technology in the Jaipur region of Rajasthan. The investigation was conducted in 2023–24, and the data was collected from 240 cooperative and private agri-input dealers from the Jaipur and Tonk districts of Rajasthan. It was revealed from the data that the highest 45.00 percent of cooperative agri input dealers had a medium knowledge level, whereas 30.00 percent and 25% of cooperative agri input dealers had low and high knowledge levels regarding Barley crops. Just contrary to that, in the case of private agri-input dealers, 42.50 % had a high knowledge level, whereas 38.33 and 19.17% of private agri-input dealers had medium and low knowledge levels. Also, it was reported that there is a significant difference in the knowledge level of cooperative & private agri-input dealers. The private agri-input dealers had more knowledge of different fields of improving barley production technology as compared to cooperative agri-input dealers.